1994
DOI: 10.1213/00000539-199408000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Morphine Combined with Epidural or Intravenous Butorphanol for Postoperative Analgesia in Pediatric Patients

Abstract: We performed a prospective, randomized, double-blinded study in 60 postoperative pediatric patients aged 6 wk to 7 yr to compare the efficacy of butorphanol given epidurally or intravenously in preventing the side effects of epidural morphine. Three groups of patients received 60 micrograms/kg epidural morphine; 20 patients also received epidural butorphanol 30 micrograms/kg, and 20 patients also received 30 micrograms/kg intravenous butorphanol. All patients were evaluated for analgesia, sedation, vomiting, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The effect of a single injection of intravenous butorphanol on the number of patients requesting rescue treatment for pruritus was evaluated in one trial. 24 The data showed that a single injection of intravenous butorphanol was not effective in decreasing the number of patients requesting rescue treatment for pruritus when compared with placebo (45% vs 40%, respectively).…”
Section: The Incidence Of Pruritusmentioning
confidence: 95%
See 4 more Smart Citations
“…The effect of a single injection of intravenous butorphanol on the number of patients requesting rescue treatment for pruritus was evaluated in one trial. 24 The data showed that a single injection of intravenous butorphanol was not effective in decreasing the number of patients requesting rescue treatment for pruritus when compared with placebo (45% vs 40%, respectively).…”
Section: The Incidence Of Pruritusmentioning
confidence: 95%
“…Ultimately, 16 valid trials were analyzed with data for 795 patients, 452 of whom received butorphanol (Table 1). [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Four of these trials involved children \ 18 years of age. [21][22][23][24] The methodological quality of the included studies Ten of the 16 included trials 13,18,[20][21][22][23][24][25][26][27] provided a sequence generation for randomization.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations